Ergonomic Evaluation of Dental Professionals as Determined by Rapid Entire Body Assessment Method in 2014 - Fatemeh Jahanimoghadam; Azadeh Horri; Naimeh Hasheminejad; Naser Hashemi Nejad; Mohammad Reza Baneshi (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: In dentistry, incorrect working posture is the most important cause of musculoskeletal disorders. Purpose: The aim of this research was to evaluate the work postures of general dentists and specialists using rapid entire body assessment (REBA) method. Materials and Method: In this cross-sectional study, work postures were assessed in 90 dentists by employing REBA method. Stratified sampling method was used. Data were analyzed by analysis of variance (ANOVA), Independent t-test and Pearson's correlation test in SPSS 19. Results: The results showed that work postures of 90% of dentists were at moderate- to high-risk levels. Among the specialists, periodontists, pedodontists and oral and maxillofacial surgeons had the worst body postures. Conclusion: In general, dentists' working postures need improvement and consequently, a more comprehensive ergonomic training and promotion is required in dentistry curriculum at Universities.